Investigation of contact surfaces between polymer matrix and metallic glasses in composite materials based on high-density polyethylene. (15th February 2016) - Zadorozhnyy, M.Yu.; Chukov, D.I.; Churyukanova, M.N.; Gorshenkov, M.V.; Zadorozhnyy, V.Yu.; Stepashkin, A.A.; Tsarkov, A.A.; Louzguine-Luzgin, D.V.; Kaloshkin, S.D.
Abstract: In our research we obtained composites based on high-density polyethylene (HDPE) reinforced with Mg67, 5 Ca5 Zn27, 5 metallic glass by co-extrusion and compression. The co-extrusion and compression procedures have been provided at temperatures of supercooled liquid temperature region of both materials (between the glass transition temperatures ( T g ) and crystallization temperature ( T x )). We investigated the mechanical properties and performed the structure characterization of the obtained polymeric/metallic glass composite samples. A positive effect of triethoxyvinylsilane on the adhesion between polymeric matrix and metallic glass reinforced particles was discovered. It was also found that composite samples (HDPE/Mg67, 5 Ca5 Zn27, 5 ) had excellent adhesion, good thermal conductivity and high modules of elasticity. The metallic glassy samples demonstrated good dimensional stability after treatment by the 10 mass% of the triethoxyvinylsilane. Graphical abstract: Highlights: Composites based on polymer and metallic glass (Mg67, 5 Ca5 Zn27, 5 ) have been obtained. Range between glass transition and crystallization temperature was used for the composites preparation. Silane improves the interaction between the polymer and the metallic glass particles. Improvement is confirmed by increasing in elastic modulus and thermal conductivity.